Method for forming iron-based wear-resistant coating on surface of TRT blade and TRT blade
By using laser welding method to form a multi-layer iron-based wear-resistant coating on the surface of the TRT blade, the problem that the wear-resistant layer in the prior art requires a transition layer and the transition layer does not have wear resistance, and higher wear resistance and longer blade life are achieved.
Patent Information
- Application Number
- CN202411788152.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art When forming a wear-resistant coating on the surface of TRT blades, a transition layer is required to avoid cracks, but the transition layer itself does not have wear resistance, resulting in a low blade life and only one wear-resistant layer is formed. Once worn through, the blade will fail.
A multi-layer iron-based wear-resistant coating was formed on the surface of the TRT blade by laser melting method, including FeCoCrNiW0.5Gd0.05, FeCoCrNiW0.4La0.06, FeCoCrNiW0.3Dy0.06 and FeCoCrNiW0.4Gd0.06 layers. By adjusting the raw material molar ratio and laser melting process parameters, a continuous defect-free wear-resistant layer was formed.
It effectively improves the surface hardness and wear resistance of TRT blades, extends the life of the blades, and avoids the problem of blade failure caused by the wear-resistant layer being worn through.
Smart Images

Figure CN119592945A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to laser coating, in particular to a method for forming an iron-based wear-resistant coating on the surface of a TRT blade and the TRT blade. Background Art
[0002] Blast furnace gas residual pressure power generation device, referred to as TRT, is a mechanical device that converts the pressure energy and thermal energy of the blast furnace top exhaust gas into electrical energy. The blade is one of the key components of the TRT device. Its working environment is harsh and the stress conditions are complex. It is very easy to produce fatigue damage during the working process. How to effectively improve the surface hardness and wear resistance of the blade, thereby increasing the life and working reliability of the blade is one of the focuses of the industry.
[0003] Prior art CN117721455A discloses a method for preparing a high-entropy alloy wear-resistant coating by ultra-high-speed laser cladding. The wear-resistant coating prepared by this method has high hardness and good wear resistance. However, our research found that this method still has defects: First, the wear-resistant coating prepared by this method requires a transition layer made of Ni625 alloy to ensure that there are no cracks on the surface of the formed high-entropy alloy wear-resistant layer. However, the thickness of the alloy layer formed on the surface of the blade has certain limitations (for example, if the film layer is too thick, due to the limitation of the interface bonding force, problems such as shedding will inevitably occur between the film layer and the substrate), and the Ni625 alloy layer itself does not have wear resistance, so the Ni625 alloy layer is equivalent to wasting the thickness that could be used to form the wear-resistant layer, which leads to a lower life of the TRT blade proposed by the prior art. Second, this method can only form a wear-resistant layer. Once the wear-resistant layer is worn through, the blade will fail immediately, which also leads to a lower life of the prior art. Summary of the invention
[0004] To achieve the above object, the present invention provides a method for forming an iron-based wear-resistant coating on the surface of a TRT blade, characterized in that the method comprises:
[0005] Step S1: Forming FeCoCrNiW on the surface of the TRT blade by laser cladding 0.5 G 0.05 layer;
[0006] Step S2: Using laser cladding method to form FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 La 0.06 layer;
[0007] Step S3: Using laser cladding method to form FeCoCrNiW 0.4 La 0.06 FeCoCrNiW is formed on the surface of the layer 0.3 Dy0.06 layer;
[0008] Step S4: Using laser cladding method to form FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G 0.06 layer.
[0009] In a preferred embodiment, for forming FeCoCrNiW 0.5 G 0.05 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Gd=1:1:1:1:0.5:0.05.
[0010] In a preferred embodiment, for forming FeCoCrNiW 0.4 La 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:La=1:1:1:1:0.4:0.06.
[0011] In a preferred embodiment, for forming FeCoCrNiW 0.3 Dy 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Dy=1:1:1:1:0.3:0.06.
[0012] In a preferred embodiment, for forming FeCoCrNiW 0.4 G 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Gd=1:1:1:1:0.4:0.06.
[0013] In a preferred embodiment, the laser cladding process of step S1 is as follows: the laser cladding power is 1500-2000W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 650-750mm / min, and FeCoCrNiW 0.5 G 0.05 The thickness of the layer is 0.5-0.6 mm.
[0014] In a preferred embodiment, the laser cladding process of step S2 is as follows: the laser cladding power is 1200-1400W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 750-850mm / min, and FeCoCrNiW 0.4 La 0.06 The thickness of the layer is 0.5-0.6 mm.
[0015] In a preferred embodiment, the laser cladding process of step S3 is as follows: the laser cladding power is 1200-1400W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 750-850mm / min, and FeCoCrNiW 0.3 Dy 0.06 The thickness of the layer is 0.5-0.6 mm.
[0016] In a preferred embodiment, the laser cladding process of step S4 is as follows: the laser cladding power is 1400-1800W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 650-750mm / min, and FeCoCrNiW 0.4 G 0.06 The thickness of the layer is 0.5-0.6 mm.
[0017] The present invention provides a TRT blade with a surface iron-based wear-resistant coating, wherein the TRT blade is formed by the method as described above.
[0018] Compared with the prior art, the present invention has the following advantages: the wear-resistant coating prepared by the prior art requires a transition layer to ensure that there are no cracks on the surface of the formed high-entropy alloy wear-resistant layer. However, the thickness of the alloy layer formed on the blade surface is limited, and the transition layer itself does not have wear resistance, so the transition layer is equivalent to wasting the thickness that could be used to form the wear-resistant layer, which leads to a lower lifespan of the TRT blade proposed by the prior art. In addition, the prior art only forms one wear-resistant layer. Once the wear-resistant layer is worn through, the blade will fail immediately, which also leads to a lower lifespan of the prior art. The method proposed by the present invention can overcome the defects of the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic structural diagram of an embodiment of the present invention.
[0020] Figure 2 It is a method flow chart of an embodiment of the present invention.
[0021] Figure 3 This is a SEM photograph of one embodiment of the present invention.
[0022] Figure 4 is a SEM photograph of another embodiment of the present invention. DETAILED DESCRIPTION
[0023] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.
[0024] Figure 1The structure diagram of an embodiment of the present invention is shown in the figure. As shown in the figure, the TRT blade formed by the method of the present invention includes: TRT blade substrate, FeCoCrNiW 0.5 G 0.05 Layer, FeCoCrNiW 0.4 La 0.06 Layer, FeCoCrNiW 0.3 Dy 0.06 Layer and FeCoCrNiW 0.4 G 0.06 layer.
[0025] Figure 2 1 is a method flow chart of an embodiment of the present invention. As shown in the figure, the method of the present invention includes the following steps:
[0026] Step S1: Forming FeCoCrNiW on the surface of the TRT blade by laser cladding 0.5 G 0.05 The method of the present invention can theoretically be used for TRT blades of various compositions. For the comparability of the results, the TRT blades of the present invention are uniformly made of 1Cr11Ni2W2MoV material; for forming FeCoCrNiW 0.5 G 0.05 The raw materials of the layers can be prepared by the following method: first, metal powders of Fe, Co, Cr, Ni, W, and Gd of corresponding weights are weighed according to the molar ratio, and then the weighed metal powders are ball-milled, and the ball mill is ground and mixed for 10 hours, and the speed of the ball mill is 200 r / min; the preparation method of the raw material metal powders used to form each wear-resistant layer in the subsequent steps is similar (the raw materials are different, but the ball milling process is the same), and will not be repeated one by one;
[0027] Step S2: Using laser cladding method to form FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 La 0.06 layer;
[0028] Step S3: Using laser cladding method to form FeCoCrNiW 0.4 La 0.06 FeCoCrNiW is formed on the surface of the layer 0.3 Dy 0.06 layer;
[0029] Step S4: Using laser cladding method to form FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G 0.06 layer.
[0030] Example 1
[0031] The following method is used to form a wear-resistant layer on the TRT blade: Step S1: FeCoCrNiW is formed on the surface of the TRT blade by laser cladding method. 0.5 G 0.05 layer; Step S2: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 La 0.06 layer; Step S3: using laser cladding method on FeCoCrNiW 0.4 La 0.06 FeCoCrNiW is formed on the surface of the layer 0.3 Dy 0.06 layer; Step S4: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G 0.06 layer.
[0032] For forming FeCoCrNiW 0.5 G 0.05 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: Gd = 1: 1: 1: 1: 0.5: 0.05. 0.4 La 0.06 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: La = 1: 1: 1: 0.4: 0.06. 0.3 Dy 0.06 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: Dy = 1: 1: 1: 0.3: 0.06. 0.4 G 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Gd=1:1:1:1:0.4:0.06.
[0033] The laser cladding process of step S1 is as follows: the laser cladding power is 1500W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 650mm / min, and the FeCoCrNiW 0.5 G 0.05The thickness of the layer is 0.5mm. It should be noted that one of the studies of the present invention focuses on the control of key parameters of the laser cladding process, and changes in other conventional laser cladding process parameters will not substantially affect the experimental results of each embodiment. For example, the laser spot diameter in each embodiment of the present invention and the comparative example is 2.2mm, the powder feeding speed is determined by the scanning speed and the thickness of each wear-resistant layer, and the powder feeding gas flow rate is determined by the powder feeding amount. The laser cladding process of step S2 is: the laser cladding power is 1200W, the argon flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 750mm / min, FeCoCrNiW 0.4 La 0.06 The thickness of the layer is 0.5 mm. The laser cladding process of step S3 is as follows: the laser cladding power is 1200 W, the argon gas flow rate is 8 L / min, the oxygen content in the gas during the cladding process is less than 50 ppm, the scanning speed is 750 mm / min, FeCoCrNiW 0.3 Dy 0.06 The thickness of the layer is 0.5 mm. The laser cladding process of step S4 is as follows: the laser cladding power is 1400 W, the argon gas flow rate is 8 L / min, the oxygen content in the gas during the cladding process is less than 50 ppm, the scanning speed is 650 mm / min, FeCoCrNiW 0.4 G 0.06 The thickness of the layer is 0.5 mm.
[0034] The surface SEM photo of Example 1 (i.e. the outermost FeCoCrNiW layer of Example 1) 0.4 G 0.06 The SEM image of the surface of the layer can be seen in Figure 3 ,from Figure 3 It can be seen that the method of the present invention can form a wear-resistant coating with a substantially flat surface and no cracks on the surface. Figure 3 It can also be seen that the FeCoCrNiW 0.4 G 0.06 There are also some potholes on the surface of the layer, but these potholes will not substantially affect the performance of the product of the present invention. The sample obtained in Example 1 is macroscopically defect-free and crack-free. It can be seen that due to the metal components used in the present invention, even if the transition layer is omitted, the present invention can form a continuous defect-free wear-resistant layer. The microhardness of Example 1 is tested, and the detection method is as follows (the detection method refers to the prior art CN117721455A): a digital microhardness tester is used to measure the microhardness of different parts of the cladding layer to the substrate of the cross section of the sample. During the measurement process, the loading load is maintained at 1.96N (HV0.2) and the loading time is 15s. Among them, FeCoCrNiW 0.4 G 0.06 The hardness of the layer is as low as 1087, FeCoCrNiW0.3 Dy 0.06 The hardness of the layer is as low as 980, FeCoCrNiW 0.4 La 0.06 The hardness of the layer is as low as 970. The wear test also refers to the prior art CN117721455A. The wear of Example 1 is 0.0057g / h. According to the process of Example 1, step S3 is executed and step S4 is omitted. At this time, the surface of the TRT blade is FeCoCrNiW 0.3 Dy 0.06 layer, and its wear amount is 0.0055g / h.
[0035] Example 2
[0036] The following method is used to form a wear-resistant layer on the TRT blade: Step S1: FeCoCrNiW is formed on the surface of the TRT blade by laser cladding method. 0.5 G 0.05 layer; Step S2: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 La 0.06 layer; Step S3: using laser cladding method on FeCoCrNiW 0.4 La 0.06 FeCoCrNiW is formed on the surface of the layer 0.3 Dy 0.06 layer; Step S4: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G 0.06 layer.
[0037] For forming FeCoCrNiW 0.5 G 0.05 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: Gd = 1: 1: 1: 1: 0.5: 0.05. 0.4 La 0.06 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: La = 1: 1: 1: 0.4: 0.06. 0.3 Dy 0.06 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: Dy = 1: 1: 1: 0.3: 0.06. 0.4 G 0.06The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Gd=1:1:1:1:0.4:0.06.
[0038] The laser cladding process of step S1 is as follows: the laser cladding power is 2000W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 750mm / min, and the FeCoCrNiW 0.5 G 0.05 The thickness of the layer is 0.6 mm.
[0039] The laser cladding process of step S2 is as follows: the laser cladding power is 1400W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 850mm / min, and the FeCoCrNiW 0.4 La 0.06 The thickness of the layer is 0.6 mm.
[0040] The laser cladding process of step S3 is as follows: the laser cladding power is 1400W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 850mm / min, and the FeCoCrNiW 0.3 Dy 0.06 The thickness of the layer is 0.6 mm.
[0041] The laser cladding process of step S4 is as follows: the laser cladding power is 1800W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 750mm / min, and the FeCoCrNiW 0.4 G 0.06 The thickness of the layer is 0.6 mm.
[0042] The surface SEM photo of Example 2 (i.e. the outermost FeCoCrNiW layer of Example 2) 0.4 G 0.06 The SEM image of the surface of the layer can be seen in Figure 4 ,from Figure 4 It can be seen that the method of the present invention can form a wear-resistant coating with a substantially flat surface and no cracks on the surface. Figure 4 It can also be seen that the FeCoCrNiW 0.4 G 0.06 There are also some pits on the surface of the layer, but these pits do not substantially affect the performance of the product of the present invention. The sample obtained in Example 2 has no defects or cracks in the macroscopic view. It can be seen that due to the metal components used in the present invention, even if the transition layer is omitted, the present invention can still form a continuous and defect-free wear-resistant layer. FeCoCrNiW 0.4 G 0.06The hardness of the layer is as low as 1098, FeCoCrNiW 0.3 Dy 0.06 The hardness of the layer is as low as 976, FeCoCrNiW 0.4 La 0.06 The hardness of the layer is as low as 981. The wear loss of Example 2 is 0.0063 g / h. The process of Example 2 is performed to step S3, and step S4 is omitted. At this time, the surface of the TRT blade is FeCoCrNiW 0.3 Dy 0.06 layer, and its wear amount is 0.0054g / h.
[0043] Example 3
[0044] The following method is used to form a wear-resistant layer on the TRT blade: Step S1: FeCoCrNiW is formed on the surface of the TRT blade by laser cladding method. 0.5 G 0.05 layer; Step S2: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 La 0.06 layer; Step S3: using laser cladding method on FeCoCrNiW 0.4 La 0.06 FeCoCrNiW is formed on the surface of the layer 0.3 Dy 0.06 layer; Step S4: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G 0.06 layer.
[0045] For forming FeCoCrNiW 0.5 G 0.05 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: Gd = 1: 1: 1: 1: 0.5: 0.05. 0.4 La 0.06 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: La = 1: 1: 1: 0.4: 0.06. 0.3 Dy 0.06 The molar ratio of the raw materials of the layer is: Fe: Co: Cr: Ni: W: Dy = 1: 1: 1: 0.3: 0.06. 0.4 G 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Gd=1:1:1:1:0.4:0.06.
[0046] The laser cladding process of step S1 is as follows: the laser cladding power is 1700W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 700mm / min, and the FeCoCrNiW 0.5 G 0.05 The thickness of the layer is 0.6 mm.
[0047] The laser cladding process of step S2 is as follows: the laser cladding power is 1300W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 800mm / min, and the FeCoCrNiW 0.4 La 0.06 The thickness of the layer is 0.6 mm.
[0048] The laser cladding process of step S3 is as follows: the laser cladding power is 1300W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 800mm / min, and the FeCoCrNiW 0.3 Dy 0.06 The thickness of the layer is 0.6 mm.
[0049] The laser cladding process of step S4 is as follows: the laser cladding power is 1600W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 700mm / min, and the FeCoCrNiW 0.4 G 0.06 The thickness of the layer is 0.6 mm. The sample obtained in Example 3 has no defects or cracks in the macroscopic view. It can be seen that due to the metal components used in the present invention, even if the transition layer is omitted, the present invention can still form a continuous and defect-free wear-resistant layer. FeCoCrNiW 0.4 G 0.06 The hardness of the layer is as low as 1058, FeCoCrNiW 0.3 Dy 0.06 The hardness of the layer is as low as 986, FeCoCrNiW 0.4 La 0.06 The hardness of the layer is as low as 975. The wear loss of Example 2 is 0.0052 g / h. The process of Example 2 is performed to step S3, and step S4 is omitted. At this time, the surface of the TRT blade is FeCoCrNiW 0.3 Dy 0.06 layer, and its wear amount is 0.0058g / h.
[0050] Comparative Example 1
[0051] The following method is used to form a wear-resistant layer on the TRT blade: Step S1: FeCoCrNiW is formed on the surface of the TRT blade by laser cladding method.0.5 G 0.05 Layer; FeCoCrNiW 0.5 G 0.05 The layer thickness is 2.4 mm, and the remaining parameters are the same as those of Example 1. The wear-resistant layer formed by the process of Comparative Example 1 has macro cracks, and the relevant samples are unqualified products, and no hardness and wear test is performed. Comparative Example 1 has cracks in the film layer due to the excessive thickness of the film layer.
[0052] Comparative Example 2
[0053] The following method is used to form a wear-resistant layer on the TRT blade: Step S1: FeCoCrNiW is formed on the surface of the TRT blade by laser cladding method. 0.5 G 0.05 layer; Step S2: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.5 La 0.1 layer; Step S3: using laser cladding method on FeCoCrNiW 0.4 La 0.06 FeCoCrNiW is formed on the surface of the layer 0.4 Dy 0.1 layer; Step S4: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G 0.06 The remaining parameters are the same as those in Example 1. The wear-resistant layer formed by the process of Comparative Example 2 has macro cracks, and the relevant samples are unqualified products, and no hardness and wear test is performed. Due to the unreasonable composition ratio of each layer in Comparative Example 2, the lattice parameters between the film layers are relatively large, which leads to increased stress between the film layers, and finally causes macro cracks in the film layer.
[0054] Comparative Example 3
[0055] The following method is used to form a wear-resistant layer on the TRT blade: Step S1: FeCoCrNiW is formed on the surface of the TRT blade by laser cladding method. 0.5 G 0.05 layer; Step S2: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 La 0.06 layer; Step S3: using laser cladding method on FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G0.06 Layer. FeCoCrNiW 0.4 La 0.06 The layer thickness is 0.6 mm; the remaining parameters are the same as those in Example 1. The wear-resistant layer formed by the process of Comparative Example 3 has macro cracks, and the relevant samples are unqualified products, and no hardness and wear test is performed. Due to the arrangement relationship of each layer in Comparative Example 3, the lattice parameters between the film layers are relatively large, which leads to increased stress between the film layers, and finally causes macro cracks in the film layer.
[0056] Comparative Example 4
[0057] The laser cladding process of step S1 is as follows: the laser cladding power is 2500W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, and the scanning speed is 850mm / min. The remaining parameters are the same as those in Example 1. The wear-resistant layer formed by the process of Comparative Example 4 does not have macro cracks, and the hardness and wear amount of the sample formed by Comparative Example 4 are tested. FeCoCrNiW 0.4 G 0.06 The hardness of the layer is as low as 1067, FeCoCrNiW 0.3 Dy 0.06 The hardness of the layer is as low as 976, FeCoCrNiW 0.4 La 0.06 The hardness of the layer is the lowest at 978. The wear loss is 0.0120g / h. The increase in wear loss in Comparative Example 4 is mainly caused by the increase in wear speed, which is mainly due to the increase in FeCoCrNiW 0.5 G 0.05 The formation process parameters of the layer are poor, resulting in FeCoCrNiW 0.5 G 0.05 The layer itself has micro defects, which cause the interfaces between the layers to be uneven and there is a large stress concentration on the interface. In the wear resistance test, since the film layer is repeatedly subjected to alternating stress, the stress concentration caused by the micro cracks on the interface causes the micro cracks to expand rapidly, which greatly accelerates the film layer loss, that is, the wear rate increases.
[0058] Comparative Example 5
[0059] The laser cladding process of step S2 is as follows: the laser cladding power is 2000W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, and the scanning speed is 950mm / min. The wear-resistant layer formed by the process of comparative example 5 does not have macro cracks, and the hardness and wear amount of the sample formed by comparative example 5 are tested. FeCoCrNiW 0.4 G 0.06 The hardness of the layer is as low as 1089, FeCoCrNiW 0.3 Dy 0.06The hardness of the layer is as low as 956, FeCoCrNiW 0.4 La 0.06 The hardness of the layer is the lowest at 745. The wear loss is 0.0131 g / h. The increase in wear loss in comparative example 5 is mainly caused by the increase in wear speed, which is mainly due to the increase in FeCoCrNiW 0.4 La 0.06 The formation process parameters of the layer are poor, resulting in FeCoCrNiW 0.4 La 0.06 The layer itself has microscopic defects, which first lead to the FeCoCrNiW 0.4 La 0.06 The hardness of the layer itself decreases, and secondly, the interfaces between the layers are not straight, and there is a large stress concentration on the interface. In the wear resistance test, the film layer is repeatedly subjected to alternating stress, and the stress concentration caused by the micro cracks on the interface makes the micro cracks expand rapidly, which greatly accelerates the film layer loss, that is, the wear rate increases.
[0060] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A method for forming an iron-based wear-resistant coating on the surface of a TRT blade, characterized in that: The method comprises: Step S1: Forming FeCoCrNiW on the surface of the TRT blade by laser cladding 0.5 G 0.05 layer; Step S2: using a laser cladding method to deposit the FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 La 0.06 layer; Step S3: using a laser cladding method to deposit the FeCoCrNiW 0.4 La 0.06 FeCoCrNiW is formed on the surface of the layer 0.3 Dy 0.06 layer; Step S4: using a laser cladding method to deposit the FeCoCrNiW 0.5 G 0.05 FeCoCrNiW is formed on the surface of the layer 0.4 G 0.06 layer.
2. The method according to claim 1, wherein: For forming the FeCoCrNiW 0.5 G 0.05 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Gd=1:1:1:1:0.5:0.
05.
3. The method according to claim 2, wherein: For forming the FeCoCrNiW 0.4 La 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:La=1:1:1:1:0.4:0.
06.
4. The method according to claim 3, wherein: For forming the FeCoCrNiW 0.3 Dy 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Dy=1:1:1:1:0.3:0.
06.
5. The method according to claim 4, wherein: For forming the FeCoCrNiW 0.4 G 0.06 The molar ratio of the raw materials of the layer is: Fe:Co:Cr:Ni:W:Gd=1:1:1:1:0.4:0.
06.
6. The method according to claim 5, wherein: The laser cladding process of step S1 is as follows: the laser cladding power is 1500-2000W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 650-750mm / min, and the FeCoCrNiW 0.5 G 0.05 The thickness of the layer is 0.5-0.6 mm.
7. The method according to claim 6, wherein: The laser cladding process of step S2 is as follows: the laser cladding power is 1200-1400W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 750-850mm / min, and the FeCoCrNiW 0.4 La 0.06 The thickness of the layer is 0.5-0.6 mm.
8. The method according to claim 7, wherein: The laser cladding process of step S3 is as follows: the laser cladding power is 1200-1400W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 750-850mm / min, and the FeCoCrNiW 0.3 Dy 0.06 The thickness of the layer is 0.5-0.6 mm.
9. The method according to claim 8, wherein: The laser cladding process of step S4 is as follows: the laser cladding power is 1400-1800W, the argon gas flow rate is 8L / min, the oxygen content in the gas during the cladding process is less than 50ppm, the scanning speed is 650-750mm / min, and the FeCoCrNiW 0.4 G 0.06 The thickness of the layer is 0.5-0.6 mm.
10. A TRT blade having an iron-based wear-resistant coating on the surface, characterized in that: The TRT blade is formed by the method according to any one of claims 1-9.
Citation Information
Patent Citations
Method for preparing high-entropy alloy wear-resistant coating by adopting ultra-high-speed laser cladding and coating
CN117721455A